The correlates of physical activity among the population aged 50-70 years (Determinantes de la actividad física entre las personas de 50 a 70 años) - Lera López, Fernando; Garrues Irisarri, Mirian A.; Suárez Fernández, María José (Retos, 2017)
Background: Physical activity is of particular interest due to its potential for improving quality of life and reducing health care costs. The contribution of this paper is to analyse the correlates of physical activity (PA) among individuals aged 50-70 years old. We differentiate between physical activity during leisure time (LTPA) and total physical activity (Total PA) and besides we offer potential policy advice to increase PA. Methods: We use a cross-sectional survey from a sample of Spanish individuals between 50 and 70 years of age. We analyse the correlates of LTPA and Total PA by estimating ordered probit models including socio-demographic characteristics, health and emotional wellbeing and social support. Results: The covariates explain in different ways LTPA and Total PA levels. In particular, the accomplishment of a minimum of LTPA is positively related to partner participation in LTPA (p<0.01), a good life satisfaction (p<0.01), being male (p<0.01) and secondary education completion (p<0.02); and it is negatively related to working status (p<0.01). On the contrary, very high levels of total PA are positively associated with partner participation (p<0.01), self-perceived health (p<0.01), women (p<0.01) and working status (p<0.05). Conclusions: It is important to increase male energy expenditure in other life domains besides leisure time. Regarding women, social support seems necessary to reach minimum levels of LTPA. Finally, the socialisation effect that we have obtained as well as the positive impact of the extrinsic social support variables might suggest the necessity to take into account couple and family variables. Resumen. Introducción: La realización de actividad física (AF) es de una indudable importancia social dado sus efectos positivos sobre la salud. Este trabajo pretende analizar los determinantes de la AF de individuos de 50-70 años. Metodología: Se emplea un estudio observacional transversal a partir de una muestra de españoles entre 50 y 70 años. Se analizan los determinantes de la AF en el tiempo libre y el total de AF mediante modelos probit ordenados, incluyendo las características sociodemográficas, de percepción de la salud física, del estado emocional y del apoyo social. Resultados: Los determinantes del total de AF y la AF realizada en el tiempo libre son distintos. La realización de un mínimo de AF en el tiempo libre está relacionada positivamente con ser hombre (p<0.01) y tener estudios secundarios (p<0.02), la participación de la pareja (p<0.01) y una buena satisfacción ante la vida (p<0.01); y negativamente con el estatus laboral (p<0.01). Por otro lado, altos niveles de AF están asociados a ser mujer (p<0.01), el estatus laboral (p<0.05), el nivel de salud percibida (p<0.01) y la participación de la pareja (p<0.01). Conclusiones: En el caso de los hombres, es importante incrementar la AF en otros ámbitos fuera del tiempo libre. En el caso de la mujer, el apoyo social resulta necesario para alcanzar unos niveles saludables de AF. Finalmente, el efecto de la socialización y el apoyo social extrínseco resultan variables relevantes que plantean la necesidad de desarrollar políticas de promoción teniendo en cuenta la situación familiar y de la pareja.